Changes in Cytomegalovirus Seroprevalence Among U.S. Children Aged 1–5 Years: The National Health and Nutrition Examination Surveys. (10th August 2020) - Petersen, Molly R; Patel, Eshan U; Abraham, Alison G; Quinn, Thomas C; Tobian, Aaron A R
Abstract: Data from the cross-sectional National Health and Nutrition Examination Surveys (NHANES) indicate that the seroprevalence of cytomegalovirus immunoglobulin G (IgG) antibodies among US children aged 1–5 years was 20.7% (95% confidence interval [CI]: 14.0, 29.0) in 2011–2012 and 28.2% (95% CI: 23.1–34.0) in 2017–2018 (adjusted prevalence difference, +7.6% [95% CI: −.4, +15.6]).